2019
DOI: 10.1590/1678-4499.2018007
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum stress tolerance in potato genotypes grown with silicon

Abstract: Potato cultivation is widespread around the world, being exposed to several abiotic stresses, including soils with high aluminum (Al) availability. Silicon (Si) is recognized for alleviating the stress caused by Al in various plant species. Thus, the aim of this study was to investigate the potential of Si to mitigate the oxidative stress caused by Al in potato genotypes, exhibiting differential sensitivity toward this element. Plants of the Al-sensitive genotype (SMIJ319-7)and Al-tolerant genotype (SMIF212-3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
(44 reference statements)
1
20
0
Order By: Relevance
“…Antioxidant enzymes and metabolites were enhanced in leaves and roots. In a similar way, Dorneles et al (2019) showed that Si was partially able to ameliorate Al toxicity in two potato genotypes. The authors related this to increased activity of antioxidant enzymes and mitigation of Al-induced damage to membrane lipids.…”
Section: What Questions Remain?mentioning
confidence: 70%
“…Antioxidant enzymes and metabolites were enhanced in leaves and roots. In a similar way, Dorneles et al (2019) showed that Si was partially able to ameliorate Al toxicity in two potato genotypes. The authors related this to increased activity of antioxidant enzymes and mitigation of Al-induced damage to membrane lipids.…”
Section: What Questions Remain?mentioning
confidence: 70%
“…Fabaceae introduction through overseeding under these conditions is often compromising, since physiological disorders can alter the main metabolic functions in plants (Abedi et al 2013;Singh et al 2017). Physiological changes make the limitation of root growth a marked effect of this element in a wide variety of plant species (Furlan et al 2018;Savic et al 2018;Silva et al 2018;Dorneles et al 2019). Adesmia latifolia, T. repens, and Trifolium pratense forage legume seedlings grown in environment subjected to 16% Al saturation have shown 65% reduction in first-order branches in comparison with those grown in environment subjected to 0% saturation (Scheffer-Basso and Prior 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In current study, root growth was reduced by 3 g l -1 nano-Al 2 O 3 , whereas this reduction was alleviated by application of exogenous Si (Figure 4). Exogenous addition of Si can mitigate toxicity symptoms induced by aluminum stress in many plant species (Hammond et al, 1995;Singh et al, 2011;Shen et al, 2014) by enhanc-ing antioxidant protection via modifying the activities of antioxidant enzymes (Shen et al, 2014;Dorneles et al, 2019), and by apoplastic binding of aluminum via formation of aluminosilicate complexes in the cell wall (Wang et al, 2004;Adrees et al, 2015). However, the mechanisms of Si-mediated alleviation of nano-Al 2 O 3 stress are still unknown.…”
Section: Si Pretreatment Ameliorated Tox-ic Effects Of Nano-al 2 O 3 mentioning
confidence: 99%
“…Si can mitigate the effects of various environmental stresses such as salinity, drought, chilling, UV radiation (Collin et al, 2014;Zhu and Gong, 2014;Habibi, 2016) and Al and Mn toxicity (Zargar et al, 2019). Exogenous application of Si exhibits the capacity to enhance the plant growth and yield as well as stress tolerance under metal toxicity by reducing the metal uptake and transport in plants (Adrees et al, 2015), formation of silicon bodies in the cell wall (Prabagar et al, 2011) and enhancing the activities of antioxidant enzymes (Habibi, 2014;Shen et al, 2014;Dorneles et al, 2019).…”
Section: Introductionmentioning
confidence: 99%